Complex Technology for Processing Some Organоmineral Waste - Kashkovsky, V.I.; Yevdokymenko, V.O.; Kamenskyh, D.S.; Tkachenko, T.V.; Vakhrin, V.V. (Science and Innovation, 2024)
Important environmental problems related to the processing of municipal wastewater sludge have been discussed. The proposed technological solution includes the following stages: sludge pretreatment; its thermal decomposition with formation of high-energy gas; production of organo-mineral fertilizers and synthetic soil; obtaining of fuel pellets; recycling of ash residue at the stage of thermal decomposition for obtaining metal oxide mixes, coagulants, construction and decorative materials.